Evaluation the effect of sesame oil on root dentin microhardness after application of chloroform and orange oil as gutta percha solvents (an in- vitro study). - Nsar Muhyaddin Aziz (Erbil Dental Journal)
Background and objectives: Gutta percha solvents like chloroform and orange oil have different effects on physio-chemical properties like the microhardness of root dentine. Aim: Effects of sesame oil on the micro hardness of root dentin after using chloroform and orange oil as guttapercha solvents. Methods: Twenty three extracted single rooted both upper and lower premolars were used crown separated from the root from the cement enamel junction ,remaining roots longitudinally sectioned from buccolingual direction each piece of roots mounted in cold cure acrylic resin and dentin surface of the roots were grounded. Micro hardness measurements were carried out before the application of gutta percha solvents. The root halves were randomly divided into 3 parallel groups (n=15), group A: was immersed in normal saline for 15 minute, group B: was immersed in chloroform for 15 minute and group C: was immersed in orange oil for 15 minute. The root halves from each group were subject to Vickers hardness test to measure micro hardness, then sesame oil were applied by bonding brush for 15 mint on each root dentin surface from all groups finally all roots subject to vicker hardness test to obtain the final micro hardness values. Results: Data were statistically analysed using one way ANOVA test and Post Hoc test (scheffe), no significant difference in reducing dentin microhardness before and after exposure to orange oil and normal saline (negative control group), (p<0.005) but significant difference before and after exposure of chloroform(p>0.005), also there was significant difference in increasing microhardness after exposure of sesame oil in the group of chloroform, but no significant difference after exposure of sesame oil and other two groups: group A,and C. Conclusion: This study showed that sesame oil can increase the microhardness of root dentin, and chloroform reduce root dentin microhardness , and can be replaced with orange oil which has no effect on dentin microhardness and on the other hand dose not have carcinogenic properties.